A Comparative Analysis of Search for and Look for in Four Corpora - Kang, Namkil (Advances in Social Sciences Research Journal, 2022)
The main goal of this paper is to compare search for and look for in the TV Corpus (TVC), the Movie Corpus (MC), the Corpus of Contemporary American English (COCA), and the British National Corpus (BNC). When it comes to the TV Corpus, it is interesting to point out that look for was preferable to search for in the TV programs of America, the UK, Canada, Australia, New Zealand, and Ireland. A further point to note is that the frequency of search for (1,898 tokens) and look for (5,423 tokens) reached a peak in the 2010s. With respect to the Movie Corpus, it is interesting to note that look for was favored over search for in the movies of six countries. More interestingly, search for (515 tokens) and look for (2,259 tokens) reached a peak in the 2010s. The COCA clearly shows that search for truth (369 tokens) and look for ways (566 tokens) are the most preferred by Americans. It is significant to note, on the other hand, that 36.36% of forty four nouns are the collocations of both search for and look for in the COCA. Similarly, the BNC shows that search for evidence (19 tokens) is the most commonly used one in the UK, whereas look for work (34 tokens) is the most widely used one. Finally, it is noteworthy that 17.64% of fifty one nouns are the collocations of both search for and look for in the BNC.